Increasing the attractiveness of surgical disciplines for students: Implications of a robot-assisted hands-on training course for medical education - Ekrutt, Jonas; Leyh-Bannurah, Sami-Ramzi; Knipper, Sophie; Schramm, Frederik; Beyer, Burkhard; Maurer, Tobias; Graefen, Markus; Budäus, Lars (Frontiers in Surgery, 2022)
Background: Structured implementation of robot-assisted surgery in the field of medical education is lacking. We assessed students’ interest in robot-assisted surgery and tested if the implementation of a hands-on robotic course into the curriculum could increase the interest to join a surgical discipline in general and especially in female students, since women are clearly underrepresented in surgical disciplines. Methods: After a prostate cancer focused seminar, 100 students were 1:1 randomized into two groups. Group B: Baseline characteristics and professional interest were assessed prior and after a hands-on robotic course, using a da Vinci® console with simulator (da Vinci® Surgical training, Intuitive Surgical Inc., USA). Group A served as post-interventional consistency control group, received the questionnaire only once after the hands-on training. Results: The male to female ratio of students was 54% and 46%. The interest to turn into urology/surgery, categorized as yes”, “no”, “maybe” changed from 18 to 16%, 36 to 30% and 46 to 54% respectively after the hands-on robotic course (p<0.001). Also, the positive attitude towards the surgical field significantly increased (20 vs 48%; p<0.001). Comparing male and female students, virtually identical proportions (23 vs. 23%) opted for joining urology or surgery as a discipline, whereas rejection (45 vs. 25%) and perchance (32 vs 50%) of that notion differed between genders (p=0.12). Conclusion: Our results demonstrate great demand for implementing robotic training into medical education for an up-to-date curriculum. Although the decision process on career choice is widely multifactorial, stereotypes associated with surgical disciplines should be eliminated. This could have a particularly positive effect on the recruitment of female medical students since women are clearly underrepresented in surgical disciplines although currently and with increasing proportions, more female students are enrolled in medical schools then male